STEAM IN EARLY CHILDHOOD: A QUANTITATIVE STUDY OF COGNITIVE DEVELOPMENT IN CHILDREN AGED 4-5 YEARS - Susi Susanti; Diana Setyaningsih; Florentina Maria Panda (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2026)
The Science, Technology, Engineering, Art, and Mathematics (STEAM) method is a learning method that emphasises the relationship between knowledge and skills. This study aims to determine the cognitive development of children aged 4-5 years before and after using the STEAM method in Kober Al Hidayah, and to determine the effect before and after using the STEAM method on the cognitive development of children aged 4-5 years in Kober Al Hidayah. The method used in this study is a quantitative method with a pre-experimental design. The results of this study show that before being given treatment in the form of using the STEAM method, the cognitive development of children aged 4-5 years in Kober Al Hidayah showed quite good results. As for after being given treatment in the form of using the STEAM method, the cognitive development of children aged 4-5 years in Kober Al Hidayah showed very good results. Meanwhile, based on the results of the t-test, it was stated that the t-calculation the t-table was 9.347 2.145 at the level of significance of 5%, of which H0 was rejected, and H1 was accepted. It means that using the STEAM method has a significant effect on the cognitive development of children aged 4-5 years in Kober Al Hidayah.